Reflecting Muslim-Christian Relations In Community Of Tegalrejo, Babadan-Ngancar-Kediri, 2019 Confronting Post-Truth - Abdullah Muslich Rizal Maulana; Asep Awaludin; Afif Gita Fauzi (USIM Press, 2024)
Vol. 24 No. 1 (2021): Journal of Islamic Social Sciences and Humanities